Analisis Faktor Sosial dan Budaya Terhadap Keputusan Pembelian Merchandise K-Pop oleh Gen Z: Penelitian - Febri Milano; Patricia Wanda; Khairur Rahmah Azjahra; Suastiana Anja Kelauri; Aditia Warman; Fahmi Aditiya; Hendra Saputra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of social and cultural factors on K-Pop merchandise purchasing decisions by Generation Z in Indonesia. Using a quantitative descriptive associative method with 55 Gen Z respondents interested in K-Pop, data were collected through an online questionnaire. The results showed that both social and cultural factors have a significant influence on K-Pop merchandise purchasing decisions. Social factors proved to be the main external driver with an average percentage of 73.38%, driven by peer influence, social media influence (especially unboxing content), and reviews from fellow fans. Meanwhile, cultural factors exert a strong internal influence with an average of 62%, mainly because merchandise is considered a symbol of identity, a source of pride (especially for limited/official editions), and a way to feel close to favorite idols. K-Pop merchandise purchasing decisions among Gen Z are the result of a dynamic interaction between the external drives of social groups (validation and interaction) and the internal motivations of fandom culture (identity, emotional meaning, and loyalty).